DETERMINANT FACTORS OF CREDIT RISK IN INDONESIAN CONVENTIONAL BANK - Alvino Nurfalah, Muhammad
During Covid-19 pandemic, the Non Performing Loan (NPL) in Indonesian bank is increasing. Reflecting from this phenomenon, this research focused on investigating the determinant factors of credit risk in Indonesian conventional bank to make sure the risk mitigation can be done in accurate manners. The methodology used in this research is panel data regression analysis using 16 conventional banks categorized in KBMI IV and KBMI III from 2018-2022. The data in this research sourced from bank financial publication data published by OJK, disclosure published in banks’ sustainability report, and macroeconomic data published by BI and BPS that collected from their official website. The result shows that there are several bank specific factors and macroeconomic factors that influenced credit risk. Bank size that is measured by total assets is significantly positively related to the credit risk. Economic, environmental, and social disclosure that is measured using GRI index disclosure, profitability that is measured using ROE, and CAR is significantly negatively related to the credit risk. However, efficiency that is measured by cost to income ratio is not significantly related to the credit risk. Inflation rates is significantly positively related to the credit risk. Interest rates and real GDP significantly negatively related to the credit risk. Meanwhile, exchange rates not significantly related to the credit risk. Based on these result, this research suggests several inputs to be considered by banks and regulators to control credit risk in bank.